Need Assessment for Master of Science in Family Nursing Curriculum: Using Delphi Technique - Yamani N. PhD; Alizadeh M. MSc; Changiz T. PhD; Taleghani F. PhD (Iran University of Medical Sciences, 2012)
Background & Aims: Our country needs nurses who are expert in family nursing. Accordingly, we need to determine their professional tasks as a basis for future planning regarding establishment of family nursing discipline in Iran. This study was a need assessment for family nursing curriculum using the viewpoints of nursing experts. Material & Methods: It was a need assessment study using Delphi technique. Study population included nursing experts such as members of nursing board in Ministry of Health and Medical Education, vice dean for education and head of the departments in nursing schools in Iran who were selected through cluster multistage sampling and 93 experts participated in the first stage of the study. Data was gathered through Delphi technique and using questionnaire in two stages. The questionnaires were send by post. Focus groups viewpoints were used to complete and finalize the tasks. Data was analyzed using SPSS- PC by calculating mean and standard deviation for each statement.Results: In the first stage of Delphi 56 items in care domain, 34 items in consultation domain, 14 items in research domain and 15 items in management domain were determined. In the second phase of Delphi all tasks received a mean score more than4. At last, 15, 11, 5, and 5 tasks were determined and finalized in care, consultation, and research and management domains, respectively. Conclusion: Findings of the study revealed the importance of family nursing role in care domain especially regarding the care of patients suffering from chronic diseases. The results of this study could be used in curriculum development of family nursing discipline.